On the Reaction Mechanism of the Selective C(sp3)–H Functionalization of N-Benzylpiperidines Mediated by TEMPO Oxoammonium Cation - Romero-Ibañez, Julio; Sandoval-Lira, Jacinto; Cruz-Gregorio, Silvano; Hernández-Pérez, Julio M.; Quintero, Leticia; Sartillo-Piscil, Fernando (Synthesis, 2023)
The selective and dual C(sp3)–H oxidation of N-heterocycles to their corresponding 3-alkoxyamino lactams mediated by TEMPO oxoammonium cation (TEMPO+) is turning into a convenient nonmetallic strategy for the rapid functionalization of piperidines and pyrrolidines to bioactive alkaloids. Mechanistic proposal suggests that TEMPO+ prefers to oxidize the endocyclic C–Hα bond of either N-substituted piperidines or pyrrolidines to their corresponding endocyclic iminium intermediates, which are transformed into enamine intermediates, and then trapped by oxoammonium cation. Although the product formation seems to be in concordance with this mechanistic rationale, neither experimental evidence nor theoretical calculations have been reported. Accordingly, the current investigation provides computational findings explaining that the origin of the selective C–Hα oxidation can be attributed to an unprecedented C–H···π interaction between two hydrogen atoms of TEMPO+ with the aromatic ring of the piperidine benzyl group. To prove the existence of the enamine intermediate, we developed an unprecedented transition-metal-free tetra C–H oxidation of two N-benzyl-4-methylenepiperidines. Accordingly, the existence of the elusive enamine intermediate was attained by generating a transitory dienamine intermediate, which was trapped by TEMPO+ and NaClO2 to give the corresponding 4-(aminooxymethyl)-3,4-epoxy-2-piperidone.
Keywords: selectivity; C–H oxidation; alkoxyamino lactams; oxoammonium salt of TEMPO; sodium chlorite